Monitor za spremljanje nenadnih ionosferskih motenj - Vogrinčič, Rok (Matrika, 2016)
A sudden ionospheric disturbance (SID) is an abnormally high ionization density in the D layer of the Earth's ionosphere caused by a Solar flare. When a Solar flare occurs on the Sun a blast of intense ultraviolet and X-ray radiation hits the dayside of the Earth. This high energy radiation is absorbed by atmospheric particles, raising them to excited states and knocking electrons free in the process of photoionization. The low-altitude ionospheric layers (D and E layer) immediately increase in electron density over the entire dayside. The ionospheric disturbance enhances very low frequency (VLF) radio propagation. With an instrument called the SID monitor, located at Astronomical Geophysical Observatory on the Golovec hill in Ljubljana, we can detect Solar flares by monitoring the signal strength of distant VLF transmitters over the course of time. The recorded SIDs indicate whether Solar flares have taken place.
Keywords: detekcija VLF valov; Earth ionosphere; ionosfera; ionosferske motnje; radijski valovi; SID monitor; solar flares; sončevi izbruhi; sudden ionospheric disturbances; VLF radio waves; Zemlja